Study the Structural and Morphological Properties of Nano/Micro Polystyrene Treated by Argon Plasma and Apply as the Antibacterial Application - Abdullah, Anmar Adel; Abed, Mohaned A.; Khalaf, Mohammed Khammass (International Journal of Computational and Experimental Science and Engineering, 2025)
In this study, plasma parameters in DC glow discharge of argon gas were used for the pure PE film untreated and exposed of argon gas plasma (10, 20 and 25) min samples treatment. X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) were studied for the morphological and structural films. X-ray diffraction patterns of all samples prepared were recorded. The XRD pattern shows the pure PE unexposed that the polycrystalline nature with strong peak around 2θ =21.51° with miller indices (110). After exposed with the argon plasma (10, 20 and 25) min and change the electrode distance (2.5, 3.5 and 4.5) cm, the new peak exhibited and the intensity of the all peaks increased with increasing exposed time, indicating that the orientation of the orthorhombic crystals had changed and also indicate the time exposed of argon plasma was affected. The increase in grain diameter average and particle size for pure PE film and exposed of argon gas plasma (10, 20 and 25) min with an increase in the treatment with dc glow discharge plasma was noted in the FESEM images. The contact angle of untreated pure PE and PE films after exposed of argon gas plasma (10, 20 and 25) min was measured at room temperature with water appeared of the contact angle results decrease with increasing time exposed plasma. The antibacterial activity for the pure PE film untreated and exposed of argon gas plasma (10, 20 and 25) min shows enhanced antibacterial activity against E. coli and S. aureus due to the changes in surface chemistry and physical structure, including increased hydrophilicity, surface roughness, and the generation of reactive species that can damage bacterial cells.